UU ITE Dalam Perspektif Perkembangan Teknologi Informasi dan Komunikasi - Rohmy, Atikah Mardhiya; Suratman, Teguh; Nihayaty, Arini Indah (Dakwah, 2021)
The industrial revolution 4.0 has an impact on the development of law, government, and social justice. The era of globalization 4.0 causes changes in almost all sectors of human life, especially the economic and technological sectors. The Information and Electronic Transaction Law, abbreviated as UU ITE, must be able to protect various legal interests to protect freedom of speech, express opinions orally and in writing. In addition, it is related to legal interests to protect the freedom of communication and obtain information as rights that are constitutional rights of citizens. The development of information and communication technology requires the government to make UU ITE. This article discusses the implementation of criminal law enforcement through UU ITE, which makes the digital world the target for applying these regulations. UU ITE must be able to bring enthusiasm to keep Indonesia's digital space clean, healthy, ethical and productive. In a criminal case with a restorative justice paradigm, the judge does not only decide based on the law alone, but also considers justice for all parties (victims, perpetrators of crimes, and the community). Court decisions should provide justice, benefit, and legal certainty, and contain philosophical, juridical and sociological foundations so that they are systematic and comprehensive. Keywords:Criminal Law, Information and Communication Technology, UU ITE